How to Increase the Growth Rate in South Africa? - Saten Kumar; Gail Pacheco; Stephanié Rossouw (Economics and Econometrics Research Institute (EERI), 2010)
Given the concern about the low growth rates in African countries, this paper deals with the issue of how to increase the said growth rates by using South Africa as a case study. This paper attempts to answer this question by examining the determinants of total factor productivity (TFP) and productivity growth. We utilise the theoretical insights from the Solow (1956) growth model and its extension by Mankiw, Romer and Weil (1992). Our empirical methodology is based on the London School of Economics Hendry's General to Specific Instrumental Variable method and Gregory and Hansen's (1996a; 1996b) structural break technique. Our findings imply that variables like human capital, trade openness, foreign direct investment, financial efficiency, democracy and financial reforms improves TFP and productivity growth in South Africa. Importantly, the key determinants appear to be democracy and financial liberalisation.
Keywords: O10; O15; 330; Solow model; total factor productivity; productivity growth